Determinants of expected poverty among rural households in Nigeria (2008)
Vulnerability measures are becoming tools for evolving proactive steps to alleviate poverty. Against this backdrop, this study examined the determinants of expected poverty (a measure of vulnerability) among rural households in Nigeria. The data for the study were obtained from the merged General Household Survey (GHS) and the National Consumer Survey (NCS) of 1996. The cross-sectional data were augmented with certain covariate factors. The data were analysed using three-stage feasible generalized least squares (3FGLS). Both idiosyncratic and covariate factors affect the expected log per capita consumption of rural Nigerians. The overall expected poverty for the country at 0.535 is 1.02 times the observed poverty in 1996. Higher expected poverty is correlated with living in the North East, no formal education, farming, older head of household, large household size and male-headed household. The North East region has both lower mean per capital consumption and higher variance compared with other regions of the country. Consumption variance is highest for households whose heads have secondary education, while households whose heads have no formal education have the lowest mean expected consumption. Farming households have lower mean per capita consumption than non-farming households. Male-headed households have both lower mean consumption and higher consumption variance relative to their female-headed counterparts. Further, household heads below age 20 have the lowest mean consumption and the highest consumption variance. Households with more than ten members have very low mean consumption and very high consumption variance. Depending on whether there is low mean consumption or higher consumption variance or both, policy strategies suitable for the different groups will vary from increased mean per capita consumption to consumption smoothening or both.